Performing a Negotiation of the Borders between the Academia, Industry and Community - Johan Awang Othman,; A. S. Hardy Shafii,; Pravina Manoharan, (Wacana Seni Journal of Arts Discourse, 2016)
A roundtable session on the topic of "Negotiating the Borders of the Academia, Industry and Community in Terms of Musical Arts" that was held in the School of The Arts, Universiti Sains Malaysia on the 24th of November 2015 was supplemented by a performance event that was meant to illustrate and reflect on the same theme. Three sets of performances were The Sound of Silence a devised play, Wayang Chulia shadow puppet performance, and Samuel J. Dass' and Michael Veerapen's solo and duo performance. By way of alluding to issues and arguments raised during the roundtable discussions, this critical review examines the varying ways that these performances demonstrate the outcome of a traversing between the academia, industry and community. It can be seen that it is possible for the practitioners of the performing arts to simultaneously represent their respective disciplines and negotiate adapting approaches and raising awareness of one another's discourses while compliant with the normalcy of the difference between the sectors of the academia, industry and community.